ANALYSIS OF DETERMINANTS TRANSFORMATIONAL LEADERSHIP AS ONE OF LEADESHIP STYLES: A SYSTEMATIC LITERATURE REVIEW - Fahira, Moona; Jayanagara, Oscar (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study systematically reviewed the current literature on transformational leadership to examine its determinants and organisational outcomes across multiple contexts. Guided by the PRISMA 2020 protocol, 20 peer-reviewed articles (2020-2025) were analysed from the original 2,000 records. Findings show that transformational leadership improves employee outcomes such as job satisfaction, organisational commitment, career development, and retention, while enhancing organisational innovation, operational excellence, and long-term competitiveness. Mediators such as communication, organisational culture, and knowledge sharing amplify the impact. Emerging themes highlight the role of leadership in sustainability, safety and digital transformation. However, the risks of elitism and centralisation of power suggest that a balanced approach to leadership is essential. Kata kunci: Transformational Leadership, Organisational Commitment, Job Satisfaction, Employee Performance Systematic Literature Review, PRISMA